2002
DOI: 10.1088/0953-4075/35/24/314
|View full text |Cite
|
Sign up to set email alerts
|

A generalization of the Keldysh Faisal Reiss model

Abstract: We calculate the ionization rate for a hydrogen atom interacting with a circularly polarized electromagnetic plane wave. Coulomb effects in the final state of the outgoing electron are taken into account. Our approximate theory is valid when the classical radius of motion of a free electron in a plane-wave field is much larger than the radius of the atom in its initial state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Coulomb effects on the sub-laser-cycle time scale, especially the Coulomb focusing [13] of the freed wave packet, were studied numerically in [14], with the emphasis on the transition between tunnelling and multiphoton ionization regimes. Analytically, including the Coulomb potential in the final state is very challenging, and many attempts have been made over the years [8][9][10][15][16][17][18][19][20][21][22][23][24][25]. The Coulomb perturbations of individual classical trajectories of the free electron in the laser field explain the asymmetries in angle-resolved above-threshold ionization (ATI) spectra [26].…”
mentioning
confidence: 99%
“…Coulomb effects on the sub-laser-cycle time scale, especially the Coulomb focusing [13] of the freed wave packet, were studied numerically in [14], with the emphasis on the transition between tunnelling and multiphoton ionization regimes. Analytically, including the Coulomb potential in the final state is very challenging, and many attempts have been made over the years [8][9][10][15][16][17][18][19][20][21][22][23][24][25]. The Coulomb perturbations of individual classical trajectories of the free electron in the laser field explain the asymmetries in angle-resolved above-threshold ionization (ATI) spectra [26].…”
mentioning
confidence: 99%
“…The importance of symmetry methods for dealing with the dynamical Stark and Zeeman effects indicates that our method might be extended to deal with such and other related problems [30,49]. The algebraic method of solution and the expression of the bound state eigenfunctions in terms of the ladder operators ± presented here may offer some simplifications in atomic physics calculations [31,41], can be useful in diverse applications in quantum optics [35,37] and it may be applied to the study of ionization states [42] by using non-discrete representations of su (1,1). But apart from the above considerations, the theory of one-electron atoms and ions has found uses in many different fields of modern physics including molecular, condensed and plasma physics, quantum optics and quantum information theory [33,38,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…As the theory of hydrogen-like atoms is useful in condensed matter [39,40] our results could be of interest there. On the other hand, they can help making contact with dynamical symmetry group techniques which are useful in atomic and molecular physics calculations [10,41], and it may, possibly, be also applied to the study of ionization states [42] by using non-discrete representations of the su(1, 1) algebra.…”
Section: Introductionmentioning
confidence: 99%
“…Such eigenfunctions, Ψ ω λ ( x , ξ) [Eq. (15)], are thus found to belong in a representation of the su (1,1) algebra, making them potentially useful in diverse quantum optics applications, in the analysis of ionization states by using nondiscrete representations of the algebra, and in the study of squeezed and coherent hydrogenic states 4, 14–17…”
Section: Introductionmentioning
confidence: 99%
“…Let us note that our technique may be useful in some other quantum chemistry calculations, it may be applied to the study of ionization states by using nondiscrete representations of su (1,1), it may found applications in studying squeezed and coherent states in the hydrogen atom 16, it may be used diversely in quantum optics, and it may be used to solve other quantum problems with chemical interest, as the 2D and the 3D harmonic oscillators, the Pöschl‐Teller potential, or the Morse potential 4, 8, 15, 17, 19–21.…”
Section: Introductionmentioning
confidence: 99%